2023
DOI: 10.1101/2023.02.22.529490
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reliability of sucrose preference testing following short or no food and water deprivation - a Systematic Review and Meta–Analysis of rat models of chronic unpredictable stress

Abstract: The sucrose preference test is a popular test for anhedonia in the chronic unpredictable stress model of depression. Yet, the test does not always produce consistent results. Long food and water deprivation before the test, while often implemented, confounds the results by introducing unwanted drives in the form of hunger and thirst. We assessed the reliability of the test when only short or no fasting was used. We searched PubMed, Embase, and Web of Science for studies in rats exposed to chronic unpredictable… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 49 publications
2
18
0
Order By: Relevance
“…A study that assessed sucrose consumption and self-stimulation thresholds in the same groups of animals failed to show that a decreased sucrose intake following chronic stress is accompanied by an increased intracranial self-stimulation 46 . In our review 6 , we found evidence of non-hedonic factors driving the consumption of sweet solutions. What is more, we observed that methodological strategies, meant to reduce bias when conducting the test (for example diminishing the effect of side preference on the test results), were often not implemented or not reported on.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…A study that assessed sucrose consumption and self-stimulation thresholds in the same groups of animals failed to show that a decreased sucrose intake following chronic stress is accompanied by an increased intracranial self-stimulation 46 . In our review 6 , we found evidence of non-hedonic factors driving the consumption of sweet solutions. What is more, we observed that methodological strategies, meant to reduce bias when conducting the test (for example diminishing the effect of side preference on the test results), were often not implemented or not reported on.…”
Section: Discussionmentioning
confidence: 74%
“…It is not uncommon to find two studies with differing durations in fasting before the test, length of the test itself, or the concentration and type of the sweet solution employed. In our review, we found the sucrose concentration to range from 0.2% to 30% (w/v) and the length of test from 15 minutes to 8 days 6 . Different sucrose concentrations and test durations were also employed in the studies that are the center of the present paper (Table 1).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations